Adaptive parameters and thermal comfort of postpartum ewes fed on concentrate supplementation in grazing system - Rocha, Ronne-von Ribeiro da; Oliveira, Petrônio Batista de; Nunes, Amaury Guimarães; Silva, Tairon Pannunzio Dias e; Pereira, Alécio Matos; Torreão, Jacira Neves da Costa (Acta Scientiarum. Animal Sciences, 2014)
Current analysis evaluated adaptive parameters and thermal comfort of postpartum ewes fed on concentrate supplementation in grazing system. Thirty lactating pluriparous sheep, 16 Santa Inês (SI) and 14 Morada Nova (MN) were used. Physiological parameters such as respiratory rate (RR), heart rate (HR) and rectal temperature (RT) were measured, in that order, with the animals at rest in the morning (6:00-7:00 am) and in the afternoon (1:00-2:00 pm), respectively, every seven days, with 10 samples. A significant effect (p < 0.05) for RR and HR was reported in the strain. Similar behavior was reported for RR between the breeds where MN sheep had high adaptability. Supplementation levels of 0.5 and 1.5% influenced (p < 0.05) RR which was stronger in the sheep that received the highest supplementation level, possibly due to calorie increase in the diet. However, HR and RT parameters did not differ within the breed due to supplementation. HR was higher between the breeds for SI sheep at 0.5%. Results show that concentrated supplementation affected the respiratory rate of ewes in the postpartum period, with higher calorie increment at 1.5% level and superiority for Santa Inês ewes. Greater adaptability of Morada Nova sheep has been indicated when fed on concentrated diet in grazing system.